PENGARUH SUHU PENYEDUHAN TERHADAP EFEK DIURETIK TEH HIJAU PADA MENCIT JANTAN GALUR SWISS - Agustina Susilowati; Nur Karim Kusuma Ramadhan (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Tea (Camelia sinensis L.) is a beverage that is familiar to the community and is drunk by brewing it. Green tea contains chemicals such as polyphenols, tannins, steroids and flavonoids. This study aimed to determine the effect of temperature brewing of green tea in the diuretic effect of male swiss strain mice. This research is an experimental study with 25 mice which were divided into five groups, group I (CMC Na 1%), Group II (Furosemide dose 5.2 mg/KgBB), Group III,IV and V (green tea brewed at 50oC,70oC dan 90oC ) with a brewing time of 5-15 minutes. Urine measurements were performed every 1 hour for 6 hours. Data analysis was carried out using the One-Way ANOVA test followed by the LSD test with a 95% confidence level. The results showed that the diuretic effect at a brewing temperature of 50oC was not significantly different (p> 0.05) with the diuretic effect at 70oC but the average volume of urine at 50oC was greater than 70oC. Diuretic effect at temperature 90oC was significantly different (p<0.05) compared to 50oC and 70oC. The diuretic effect of green tea can be optimal, if the brewed at a temperature of 50oC and 70oC for 5-15 minutes.